Estrategias didácticas que contribuyan al desarrollo de las competencias tecnológicas de los cursos 1º, 2º, 3º, 4º y 5º del Colegio Arrulladito de San Juan del Cesar La Guajira. - Gómez Cabana, Yakelin Paola (Universidad Antonio Nariño, 2022)
The present work focuses on an investigation developed in grades primary basic of the Arrulladitos School, in San Juan del Cesár, department of La Guajira, where didactic strategies are proposed that will allow the improvement of skills and technological capacities of the children of these courses, based on clear objectives to be developed, which are supported by the application of appropriate strategies to the children's learning process, the characterization of technological tools necessary for the development of said strategies and the proposal of a monitoring plan that continues the methodology used by the practitioner, this being a qualitative research that ends up showing in its results that the proposed strategies effectively comply with what is proposed, and bring with them a group of students with developed and strengthened skills through this methodology applied by the counselor.